Gender and Rural Non-farm Entrepreneurship - Rijkers, Bob; Costa, Rita (World Bank, Washington, DC, 2012)
Despite their increasing prominence in policy debates, little is known about gender inequities in non-agricultural labor market outcomes in rural areas. Using matched household-enterprise-community data sets from Bangladesh, Ethiopia, Indonesia and Sri Lanka, this paper documents and analyzes gender differences in the individual portfolio choice and productivity of non-farm entrepreneurship. Except for Ethiopia, women are less likely than men to become nonfarm entrepreneurs. Women's nonfarm entrepreneurship isn't strongly correlated with household composition or educational attainment, but is especially prevalent amongst women who are the head of their household. Female-led firms are much smaller and less productive on average, though gender differences in productivity vary dramatically across countries. Mean differences in log output per worker suggest that male firms are roughly 10 times as productive as female firms in Bangladesh, three times as those in Ethiopia and twice as those in Sri Lanka. By contrast, no significant differences in labor productivity were detected in Indonesia. Differences in output per worker are overwhelmingly accounted for by sorting by sector and size. They can't be explained by differences in capital intensity, human capital or the local investment climate, nor by increasing returns to scale.